Survey of Clinical Practice for Irritable Bowel Syndrome in East Asian Countries - Fukudo, Shin; Hahm, Ki-Baik; Zhu, Qi; Sollano, Jose D.; Rani, Abdul A.; Syam, Ari F.; Kachintorn, Udom; Suzuki, Hidekazu; Kamiya, Takeshi; Joh, Takashi; Uchiyama, Kazuhiko; Naito, Yuji; et al. (Digestion, 2015)
Aim: Sociocultural factors are important because their different effects on the features of irritable bowel syndrome (IBS) between countries will provide clues towards solving this problem. The aims of this study were to depict the clinical realities of IBS in East Asian countries and test the hypothesis that the diagnosis and treatment of IBS differ between countries. Subjects and Methods: Study participants were 251 physicians involved in the clinical practice of IBS at major institutions in Japan, South Korea, China, the Philippines, Indonesia and Singapore. The questionnaire contained 45 questions focused on the clinical practice of IBS. Results: Subjects in Japan, South Korea, China, Indonesia, the Philippines and Singapore accounted for 55.4, 17.9, 8.8, 8.0, 6.4 and 3.6% of the study cohort, respectively. Amongst East Asian physicians, the most important symptom was considered to be abdominal pain by 33.4%, whilst 24.3% regarded alternating diarrhea and constipation to be the most important symptoms. Total colonoscopy and histopathology use showed no difference among countries. Prescriptions given for mild (p < 0.0001), moderate (p < 0.0001), severe (p < 0.0001), intractable (p = 0.002), diarrheal (p < 0.0001) and constipating (p < 0.0001) patients with IBS significantly differed between the countries. Except for several minor points, IBS specialists showed no significant difference in their diagnosis and treatment of IBS when compared to nonspecialists. Conclusion: This survey provided data on the clinical treatment of IBS among East Asian countries. The results supported the hypothesis that the diagnosis and treatment of IBS differs between countries.